Differential HLA Association of GAD65 and IA2 Autoantibodies in North Indian Type 1 Diabetes Patients. (27th December 2021) - Chuzho, Neihenuo; Kumar, Neeraj; Mishra, Neetu; Tandon, Nikhil; Kanga, Uma; Kaur, Gurvinder; Singh, Paras; Mishra, Gunja; Sharma, Shreya; Mehra, Narinder K.
Abstract : The human leucocyte antigen (HLA) association with type 1 diabetes (T1D) is well known but there are limited studies investigating the association between β -cell autoantibodies and HLA genes. We evaluated the prevalence of GAD65 and IA-2 autoantibodies (GADA and IA2A) in 252 T1D patients from North India and investigated the genetic association of GADA and IA2A with HLA class I and class II genes/haplotypes. GADA and IA2A were detected in 50.79% and 15.87% of T1D patients, respectively, while only 8.73% had both GADA and IA2A. HLA-DRB1 ∗ 03 was observed to be significantly higher in GADA+ T1D patients as compared to GADA– (91.41% vs. 66.13%, Bonferroni-corrected P P c = 1.11 × 10 − 5 ; OR = 5.45 ; 95% CI: 2.67-11.08). Similarly, HLA-DQB1 ∗ 02 was found to be significantly increased in GADA+ patients (94.53%, P c = 2.19 × 10 − 5 ; OR = 6.27 ; 95% CI: 2.7-14.49) as compared to GADA– (73.39%). The frequencies of HLA-DRB1 ∗ 04 and DQB1 ∗ 03 were increased in IA2A+ patients (45.0% and 52.5%, respectively) as compared to that in IA2A– (25.94% and 33.96%, respectively). Further, the frequency of DRB1 ∗ 03-DQB1 ∗ 02 haplotype was found to be significantly increased in GADA+ T1D patients as compared to GADA- (60.55% vs. 41.94%, P = 3.94 × 10 − 5 ; OR = 2.13 ; 95 % CI = 1.49 -3.03). Similarly, HLA-DRB1 ∗ 04-DQB1 ∗ 03 haplotype was found to be significantly increased in IA2A+ T1D patients compared to IA2A– patients (22.5% vs. 12.97%; P = 0.041 ; OR = 1.95 ; 95 % CI = 1.08 -3.52). None of the HLA class I genes (HLA-A, B, and Cw) was found to be associated with GADA or IA2A in people with T1D. Our findings suggest that HLA-DRB1 ∗ 03/DQB1 ∗ 02 and HLA-DRB1 ∗ 04/DQB1 ∗ 03 might play an important role in the development of GADA and IA2A, respectively.